Progress on Bioavailability of Calcium and Calcium-Peptide Complexes - Jiachen LIU; Yongqiang CHENG; Ning TANG (Shipin gongye ke-ji, 2023)
Calcium is an essential nutrient for human health and plays a crucial role in various physiological processes such as bone formation, muscle contraction, nerve transmission, and blood clotting. Calcium absorption mainly occurs in the small intestine where the calcium enters the enterocytes through active transport or passive diffusion. However, the free calcium ions dissolved in gastric acid may form insoluble precipitates with other dietary components (such as phytate, oxalate, fiber) in the slightly alkaline intestinal environment, leading to decreased calcium absorption and bioavailability. Decreased calcium absorption can result in a range of bone metabolic diseases, such as rickets and osteoporosis. Therefore, it is important to choose foods or supplements that can provide highly soluble and bioavailable forms of calcium. Some organic calcium salts such as calcium gluconate and calcium citrate have been shown to form supersaturated solutions in the intestinal tract, which can enhance calcium absorption by increasing the concentration gradient across the intestinal epithelium. Furthermore, calcium-peptide complexes are proven to be very effective for improving calcium absorption without causing any side effects. Calcium-peptide complexes can serve as a novel calcium supplement. In this paper, the effects of food components on calcium absorption and bioavailability are reviewd, and the mechanisms underlying the enhancement of calcium absorption by some organic salts (such as calcium gluconate and calcium citrate) and peptides are summarized. And the potential applications of calcium-peptide complexes in human nutrition are also discussed, aiming to provide new insights that can aid in the development of safe and effective calcium supplements